2016
DOI: 10.1038/jid.2015.352
|View full text |Cite
|
Sign up to set email alerts
|

Type VI Collagen Regulates Dermal Matrix Assembly and Fibroblast Motility

Abstract: Type VI collagen is a non-fibrillar collagen expressed in many connective tissues and implicated in extracellular matrix (ECM) organisation. We hypothesized that type VI collagen regulates matrix assembly and cell function within the dermis of the skin. In the present study we examined the expression pattern of type VI collagen in normal and wounded skin and investigated its specific function in new matrix deposition by human dermal fibroblasts. Type VI collagen was expressed throughout the dermis of intact hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 50 publications
4
79
0
8
Order By: Relevance
“…Collagen VI, like fibronectin, is an ECM protein downregulated in irradiated skin (fold-change 0.54). In a study of cell-derived matrices deficient in the protein, collagen VI was critically associated with assembly of the dermal matrix and motility of resident fibroblasts, suggesting that downregulation may limit wound healing 39 . P27(Kip1) is an enzyme inhibitor that controls cell cycle progression and has been shown to play a supervisory role in preventing hyperproliferation during tissue repair 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Collagen VI, like fibronectin, is an ECM protein downregulated in irradiated skin (fold-change 0.54). In a study of cell-derived matrices deficient in the protein, collagen VI was critically associated with assembly of the dermal matrix and motility of resident fibroblasts, suggesting that downregulation may limit wound healing 39 . P27(Kip1) is an enzyme inhibitor that controls cell cycle progression and has been shown to play a supervisory role in preventing hyperproliferation during tissue repair 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Collagen VI is a critical component in maintaining the integrity of the skin, promoting roles such as organization and communication between cells. Recently, it has been found that collagen VI regulates the organization and composition of de novo ECM within the skin, suggesting a key role in wound healing and tissue repair (15). Therefore, its alteration appears to make skin susceptible to a variety of abnormalities, including spontaneous keloids, which are part of the clinical spectrum of skin alterations related to COL6-RD.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen VI deficient matrices are thinner and contain less total collagen than matrices derived from healthy individuals. Collagen VI also affects cell spreading and migration [10]. Interestingly, macrophages secrete collagen type VI to modify cell-matrix interactions during wound healing [11].…”
Section: Matrix Deposition and Dynamics In The Wound Healing Cascadementioning
confidence: 99%